Influences of Musicology and Ethnomusicology in Music Education Research in Brazil - Eliton Perpetuo Rosa Pereira (Per Musi, 2023)
The text presents a theoretical synthesis of the musicological and ethnomusicological tendencies with the objective of exploring these categories in the context of the research in musical education, which approaches music in the school. Thirty theses were chosen for the application of these categories with codified cuts, mostly in the abstracts of the works. The methodologies of Categorical Content Analysis and Qualitative Research Synthesis were used to give security to the qualitative analysis process of theses. This exploratory and descriptive work revealed fundamental aspects about the influence of musicology and ethnomusicology in the research in musical education in Brazil. The chosen categories of the theoretical contexts of musicology and ethnomusicology and the processes of analysis presented may enable new forms of understanding of the area of musical education as a field of pedagogical knowledge and also (ethno)musicological.